THE EFFECT OF ENTREPRENEURSHIP EDUCATION AND THE USE OF SOCIAL MEDIA ON STUDENTS’ ENTREPRENEURIAL INTENTION IN JAKARTA - Amalia Putri Maharani; Yohana, Corry; Pratama, Aditya (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2023)
The purpose of this study was to determine the effect of entrepreneurship education and the use of social media on student entrepreneurial intention in Jakarta. The research method used is a survey method with a quantitative approach, the population used is students with campus domicile in Jakarta and active in using social media. The data analysis technique used is multiple linear regression analysis using the IBM SPSS version 25. The first test carried out was the validity and reliability test of the instrument with the results of the validity test p-value 0.000 <0.05 and the reliability test results with Cronbach's alpha value of 0.985 > 0.6. The second test is the classical assumption test, all data in this study pass the classical assumption test. The next test is multiple linear regression analysis obtained by the equation Y = 1.024 + 0.332 X1 + 0.495 X2 + e. The next test is hypothesis testing with t-test obtained a significance value of 0.000 <0.05 and f-test with a significance value of 0.000 <0.05. The results of this study are all hypotheses can be accepted.